Analysis of Power and Efficiency of a Three-Stage Four-Blade Savonius Wind Turbine with Variations in Load and Wind Speed - Gerald Adityo Pohan; Gerardus Dharma Sandiawan; Febi Rahmadianto; Tito Arif Sutrisno (Universitas Panca Marga, 2025)
The wind potential in Indonesia generally has low wind speeds ranging from 3 m/s to 7 m/s, making vertical-axis wind turbines very suitable for use under such low-wind-speed conditions. Therefore, the concept of developing a device emerged—designing a laboratory-scale Savonius wind turbine utilizing a wind tunnel so that a multi-stage windmill can operate using a 3D printing method. The testing was carried out using the observational method, which involved directly observing the object under study—in this case, a four-blade Savonius wind turbine—to determine the power output at specific wind speeds and loads using a wind tunnel. The experiment used two load variations of 0.01 kg and 0.02 kg at wind speeds of 6 m/s and 7 m/s. At wind speeds of 6 m/s and 7 m/s, the turbine produced shaft rotations of 427 rpm, 259 rpm, 359 rpm, and 305 rpm with loads of 0.01 kg and 0.02 kg. For the four-blade configuration, the wind speeds of 6 m/s and 7 m/s generated turbine power outputs of 10.033 W and 6.318 W with loads of 0.01 kg and 0.02 kg, respectively. At wind speeds of 6 m/s and 7 m/s with loads of 0.01 kg and 0.02 kg, the turbine efficiencies were 0.707%, 0.682%, 1.193%, and 1.611%. For the four-blade configuration at 6 m/s and 7 m/s with loads of 0.01 kg and 0.02 kg, the generator power outputs were 7.08 W, 0 W, 3.29 W, and 0 W, respectively. Based on the test results and data analysis—including wind turbine rotational speed, turbine power, generator power, and turbine efficiency—the findings show a directly proportional relationship. Therefore, the higher the number of blades, the greater the turbine’s rotational speed, turbine power, generator power, and efficiency.